Selection of trees for rubbing by red and roe deer in forest plantations - Ramos, Jaime A. (2006)
Antler rubbing is a form of behaviour by which deer may damage and ultimately induce mortality of trees. Understanding factors affecting selection of trees for rubbing may contribute to mitigation of negative effects of such behaviour in plantations or woodlands. We analysed characteristics of trees rubbed by red and roe deer along transects established in plantations of Pinus pinaster (Aiton), Pseudotsuga menziesii (Mirbel) Franco, Betula alba L. and Quercus robur L. in Northeast Portugal. Transects were walked during five sampling periods covering mating seasons of red and roe deer. Red deer preferentially rubbed trees adjacent to the edge of plantations and large clearings whilst roe deer selected those inside plantations within small clearings. There was seasonal segregation in the number of trees rubbed by each deer species with red deer rubbing trees mainly between September and February and roe deer mainly between December and June. Both red and roe deer selected trees with smaller diameter than those of available trees although trees selected by red deer had larger diameters than those selected by roe deer. Roe, but not red deer, tended to avoid trees protected by shrubs. Overall, the selection of trees for rubbing was site-dependent suggesting that generalizations across sites should be made with caution. Mitigating measures, such as deer control, tree protection or provision of alternative rubbing posts should target stands of particular tree species, location of trees in relation to stand clearings and tree size classes.